Let-7a induces metabolic reprogramming in breast cancer cells via targeting mitochondrial encoded ND4 - Praveen Sharma (BMC, 2021)
Abstract Background and objectives MicroRNA (miRNA) that translocate from the nucleus to mitochondria are referred to as mitochondrial microRNA (mitomiR). Albeit mitomiRs have been shown to modulate gene expression, their functional impact within mitochondria is unknown. The main objective of this study is to investigate whether the mitochondrial genome is regulated by miR present inside the mitochondria. Methods and results Here, we report mitomiR let-7a regulates mitochondrial transcription in breast cancer cells and reprogram the metabolism accordingly. These effects were mediated through the interaction of let-7a with mtDNA, as studied by RNA pull-down assays, altering the activity of Complex I in a cell line-specific manner. Our study, for the first time, identifies the role of mitomiR (let-7a) in regulating the mitochondrial genome by transcriptional repression and its contribution to regulating mitochondrial metabolism of breast cancer cells. Conclusion These findings uncover a novel mechanism by which mitomiR regulates mitochondrial transcription.